Pengaruh Jumlah Penduduk dan Pengangguran Terhadap Pertumbuhan Ekonomi di Kabupaten Bulukumba - Putri, Rini Dwi; Naidah, Naidah; Suarni, Agusdiwana (EKOMBIS: JURNAL FAKULTAS EKONOMI, 2025)
This study aims to analyze the effect of Population and Unemployment on Economic Growth in Bulukumba Regency. Ecoomic growth is an important indicator in assessing the development performance of a region, which is influenced by various factors, including the dynamics of population. The type of data used in this research is quantitative data obtained from time series data from 2010 t0 2024. The data used in this research is secondary data obtained from the Central Bureau of Statistics (BPS) of Bulukumba Regency. The analysis method used is multiple linear regression to test the relationship between the independent variable (population and unemployment) on the dependent variable (economic growth). The results showed that population has a positive and significant effect on economic growth, while unemployment has a negative but insignificant effect on economic growth.Keywords : Population; Unemployment Rate; Economic Growth